A new simplified calculation model of CFS composite exterior walls under fire conditions. (December 2019) - Chen, Wenwen; Ye, Jihong
Abstract: Cold-formed steel (CFS) composite exterior walls are made of cold-formed, thin-walled steel lipped channel studs with board linings on both sides. There are limited data on the structural and thermal performance of CFS composite exterior walls under fire conditions, especially from simulation analysis, in contrast with the data available for interior walls. Therefore, a new simplified model was proposed in this paper to accurately simulate exterior walls exposed to fire on one side; in this model, spring elements were applied to provide out-of-plane constraints different from the constraints of the simplified model for interior walls previously proposed. A discussion of the numerical simulation results of studs with different parameters, including temperature-rise curves, vertical load ratios, screw spacings, steel grades and cross-sectional sizes, was conducted to determine the range of the spring stiffness. Finally, the developed model was validated using the fire test results of two CFS exterior walls, where one had an external panel made of oriented strand boards and the other had an external panel made of autoclaved lightweight concrete boards.